2013
DOI: 10.1530/eje-13-0136
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in Endocrinology: Autosomal dominant osteopetrosis revisited: lessons from recent studies

Abstract: Systematic studies of autosomal dominant osteopetrosis (ADO) were followed by the identification of underlying mutations giving unique possibilities to perform translational studies. What was previously designated ADO1 turned out to be a high bone mass phenotype caused by a missense mutation in the first propeller of LRP5, a region of importance for binding inhibitory proteins. Thereby, ADO1 cannot be regarded as a classical form of osteopetrosis but must now be considered a disease of LRP5 activation. ADO (Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 208 publications
(322 reference statements)
1
63
0
Order By: Relevance
“…The ADO II patients had a total of six different CLCN7 mutations, half of them localized in the C-terminal domain of the protein (Figure 1a). 33 The most frequent mutations responsible for ADO II 10,23 were also represented in our patient group: five related patients had the p.G215R mutation and three unrelated patients the p.R767W mutation. All the patients had a higher than normal (2-5 U/ml) serum TRAP level, with values ranging from 5.3 to 60.9 U/ml (mean value 33.9 ± 9.3 U/ml) (Figure 1b).…”
Section: The Patients Exhibit a Typical Ado II Phenotypementioning
confidence: 67%
“…The ADO II patients had a total of six different CLCN7 mutations, half of them localized in the C-terminal domain of the protein (Figure 1a). 33 The most frequent mutations responsible for ADO II 10,23 were also represented in our patient group: five related patients had the p.G215R mutation and three unrelated patients the p.R767W mutation. All the patients had a higher than normal (2-5 U/ml) serum TRAP level, with values ranging from 5.3 to 60.9 U/ml (mean value 33.9 ± 9.3 U/ml) (Figure 1b).…”
Section: The Patients Exhibit a Typical Ado II Phenotypementioning
confidence: 67%
“…There is a very high fracture rate in recessive patients due to poor quality of the non-remodeled bone (3)(4)(5)7). Moreover, these fractures show defective healing.…”
Section: Recessive Osteopetrosesmentioning
confidence: 99%
“…Mutations in the gene coding for carbonic anhydrase tend instead to result in a more moderate phenotype, but with cognitive disabilities, as well as other morbidities (6). The dominant form of osteopetrosis, due to dominant negative mutations in the CLCN7 gene, can result in mild, moderate, but also severe disease, although with less infirmities than autosomal recessive forms (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the ADO I form presents with a more generalized sclerosis (not the bone-within-bone typical of ADO II), which is especially pronounced in the cranial vault, and has been shown to be due to a number of different mutations in LRP5. 72,85 The fact that a bone formation gene/pathway, which principally acts in the osteoblast lineage, calls into question whether ADO I is correctly associated with osteopetrosis? Studies in mice and bone cell lines [86][87][88][89][90][91][92][93] have shown that Wnt/b-catenin signaling in osteoblasts/osteocytes controls the expression regulators of osteoclastogenesis (for example, osteoprotegerin and RANKL).…”
mentioning
confidence: 99%
“…Studies in mice and bone cell lines [86][87][88][89][90][91][92][93] have shown that Wnt/b-catenin signaling in osteoblasts/osteocytes controls the expression regulators of osteoclastogenesis (for example, osteoprotegerin and RANKL). Thus while ADO I has the appearance of an osteopetrotic condition, 85 the primary defect is acting at the osteoblast/ osteocyte cell level, which begs the question of how best to classify the disease. Given the genetic basis of ADO I, perhaps it should be more appropriately categorized as an osteosclerotic phenotype as suggested by de Vernejoul.…”
mentioning
confidence: 99%